Certain Blood Lipid Profile and Immunological Alterations Accompanied Vascular Inflammation in Hypertensive Patients - Lamees M. Al-Janabi (Journal of Global Pharma Technology, 2016)
The current study was conducted to examine certain blood biochemical and immunological changes associated with high blood pressure in hypertensive patients. Hundred blood samples were collected from normal and hypertensive people, at Al-Hussein teaching Hospital, for assessment of Fatty lipids such as total cholesterol, triglyceride, low-density lipoprotein, and high-density lipoprotein as well as the study of IL-1β and TNF-α genes expression levels. The results of hypertensive patients showed significant increase of T. Cholesterol , TG and LDL and significant decrease of HDL, whereas the molecular analysis revealed significant increase in the expression ranks of both IL-1ß and TNF-ɑ genes in comparison with normal people. In conclusion, hypertension could be accompanied by lipidemia and decreased immunity.Keywords: Hypertension, Lipid profile, Immunity IL-1β, TNF-α.